Radiation dose assessment of 7Be and activated corrosion products present in the hydrogen trap of IFMIF-DONES lithium system - Martínez-Serrano, José Javier; Qiu, Yuefeng; Dézsi, Tomás; Nitti, Francesco Saverio; Ibarra, Ángel (Elsevier, 2024)
The radiological impact that 7Be and activated corrosion products (ACP) dissolved in Li could have in normal operation and maintenance in the surroundings of the hydrogen trap (HT) of future IFMIF-DONES facility has been assessed. Ambient dose equivalent rates were calculated with radiation transport program MCNP at half height of trap. Four different Y contents were considered in the trap: 1, 3, 5 and 8 kg. In normal operation dose rates in the range 13.7–15.1 mSv/h have been found in contact with the trap and 0.28–0.31 mSv/h at 1 m of the trap. 7Be has a very low contribution to dose (3–3.7 µSv/h). Dose simulations have shown that a concrete wall 30 cm thick can reduce dose rates to acceptable dose limits. In maintenance operation the trap is drained and Li film remains attached to Y pebbles. Three possible Li film thickness have been considered: 10, 50 and 100 µm. Estimated 7Be activity is below exemption limits during maintenance. Assessed dose rates are in the range 34–1420 µSv/h at contact with the trap and a maximum of 10.9 µSv/h at 1 m of the trap.
Keywords: Radiación; Corrosión; Hidrógeno; Ambient dose equivalent rate; Hydrogen trap; 7Be; Activated corrosion product; IFMIF-DONES